Smart Aging: Harnessing Artificial Intelligence to Enhance Elderly Health Care and Independence - Rahul Garg (Journal of the Indian Academy of Geriatrics)
The rapidly aging global population presents significant challenges to healthcare systems worldwide. This review explores the transformative role of artificial intelligence (AI) in addressing the complex healthcare needs of the elderly. AI applications in elderly health care span various domains, including diagnostics and disease prediction, personalized treatment planning, remote monitoring, cognitive assistance, fall prevention, and medication management. The integration of AI technologies offers numerous benefits, such as improved diagnostic accuracy, enhanced personalization of care, continuous health monitoring, and support for independent living. However, the implementation of AI in elderly health care also faces challenges related to data privacy, ethical considerations, technology adoption, and regulatory frameworks. Future directions in this field include advancements in natural language processing, multi-modal data integration, and the development of explainable AI systems. As AI continues to evolve, its potential to improve the quality of life and health outcomes for older adults is substantial. This review underscores the importance of collaborative efforts between healthcare providers, technologists, policymakers, and elderly individuals to fully realize the benefits of AI in elderly health care when addressing associated challenges.